Detector bandwidth and polarization switching rates: spectrophotometric observations of the Sun by the Birmingham Solar Oscillations Network. Issue 1 (20th March 2023) - Hale, S J; Chaplin, W J; Davies, G R; Elsworth, Y P; Howe, R
Abstract: The Birmingham Solar Oscillations Network (BiSON) observes acoustic oscillations of the Sun. The dominant noise source is caused by fluctuations of Earth's atmosphere, and BiSON seeks to mitigate this effect by combining multiple rapid observations in alternating polarization states. Current instrumentation uses bespoke Pockels-effect cells to select the polarization state. Here, we investigate an alternative off-the-shelf solution, a liquid crystal (LC) retarder, and discuss the potential impact of differences in performance. We show through electrical simulation of the photodiode-based detectors, and assessment of both types of polarization device, that although the switching rate is slower the off-the-shelf LC retarder is a viable replacement for a bespoke Pockels-effect cell. The simplifications arising from the use of off-the-shelf components allow easier and quicker instrumentation deployment.